Gm-Realization of Controlled-Gain Current Follower Transconductance Amplifier - Worapong Tangsrirat (The Scientific World Journal)
This paper describes the conception of the current follower transconductance amplifier (CFTA) with electronically and linearly current tunable. The newly modified element is realized based on the use of transconductance cells (Gms) as core circuits. The advantage of this element is that the current transfer ratios (iz/ip and ix/iz) can be tuned electronically and linearly by adjusting external DC bias currents. The circuit is designed and analyzed in 0.35 μm TSMC CMOS technology. Simulation results for the circuit with ±1.25 V supply voltages show that it consumes only 0.43 mw quiescent power with 70 MHz bandwidth. As an application example, a current-mode KHN biquad filter is designed and simulated.